POTENSI TANIN DARI HUTAN PAYAU TARAKAN, KALIMANTAN TIMUR - Suwardi Sumadiwangsa; Yacob Ando (Jurnal Penelitian Hasil Hutan, 1986)
Mangrove forest  grows  widely distributed  throughout  Indonesia,  and one of the most promising  resource is in East Kalimantan.Until recently the utilization of mangrove forest  is only for  wood,  while the bark is wasted, although  various literatures have indicated that the tanning  material found   in the bark can be a intesfactory  component  for  glue manufacture.This paper presents a survey result on the standing stock of 11 mangrove species at the Forest District of Bulongan  in East Kalimantan.   The survey was based on a 25% sampling intensity  which is jointly  conducted  both by PT Karyasa Kencana and District of Forestry at Bulongan,  East Kalimantan.   The tannin  content  of  the bark  were determined  at the Forest Product  Research and Development   Centre Laboratory  in Bogor. In  this  Province,   the  mayor   tannin  producing   mangroves   are  Bruguiera caryophylloides,    Rhizophora macronata,    and   Bruguiera gymnorrhiza.